Incongruencia entre el Inciso Segundo del Art.146 y el Art 65 del Código Orgánico Integral Penal, acerca del Proceso de Habilitación para volver a ejercer la Profesión luego de cumplida la pena en los Delitos de Homicidio Culposo por Mala Práctica Profesional - Ramón Picoita, Oscar Patricio (2017)
In the present research is to demonstrate the existence of an inconsistency between Article 65 and the second paragraph of 146 of the COIP , when setting the time of the accessory penalty and processes for the new qualification for professional practice , which it creates a contradiction , which in turn violates rights of professionals who commit the crime of manslaughter by malpractice , albeit the criminalization of malpractice was a need and a recommendation by the Commission American Commission on Human Rights (CIDH ) , also found this provision in the Constitution of the Republic , in force since 2008 in its second paragraph, Article 54 , which states; "People will be responsible for malpractice in the exercise of their profession , trade or occupation , especially that which threatens the integrity or lives of people . " That is why , one should establish the malpractice as a crime , constituting an autonomous crime in the new COIP , which is manslaughter for malpractice , conduct which was previously sanctioned as involuntary manslaughter with the old penal code, that was unrelated to what the Constitution mandates , ie the characterization of this behavior in the new criminal law ( COIP ) was necessary , this new offense should be clear and precise according to what the Constitution mandates guaranteeing legal certainty , due process and the right to equality , formal, material non-discrimination and the principles of legality taxatividad and subject to criminal law, which does not occur in what you have q do with the additional penalty because it is not established or the 5 time or processes for the new qualification after the fulfillment of the custodial sentence which even contradicts the provisions of article 65 of the same law COIP , which states that the time of disqualification will be determined in each criminal, time is not prescribed in the crime of murder culpable for malpractice because only is set the time range of imprisonment , nor are established processes enable to return to practice in the COIP , or any other law of the Ecuadorian legal system is why necessarily warrants a legal and doctrinal analysis of these rules , which is made in the review of the literature and is corroborated by the field study , surveys and interviews that would support such claims , and the presentation of a proposal for reform remedy this problem